Esthetical Properties of Single-Shade and Multishade Composites in Posterior Teeth - Graziela R. Batista; Alessandra B. Borges; Rayssa F. Zanatta; Cesar R. Pucci; Carlos R. G. Torres (Hindawi Limited, 2023)
This study aimed to compare the aesthetic properties of posterior composite restorations made with a multishade (MS) or single-shade (SS) material. For that, 23 extracted human molars were used. The shade determination was performed, and the occlusal anatomy was registered by a custom-made stamp. Then, class I preparations were made, and each tooth was restored twice, using two different composites of MS/opacity layering material (Admira Fusion-Voco) and an SS/opacity bulk-fill composite (Admira Fusion X-tra-Voco). After finishing the first restoration with the MS material, a standardized picture was taken, and the restoration was removed. Then, the preparation was restored again with the other composite, obtaining a new picture. The pictures were randomly analyzed by 10 calibrated evaluators regarding color match using the FDI criteria. The evaluators were blinded to the restorative material used. Data were analyzed using an unpaired t-test and Wilcoxon test. The significance level adopted in the study was 5%. As a result, there were nonsignificant differences between the composites evaluated for color match, as well nonsignificant differences were obtained related to which restorative technique produced the best aesthetic results. Only for darker shades (A4, B4, and C4), most of the evaluators considered the restorations made with the MS material more aesthetic than with the SS, while for the other shades, nonsignificant differences were observed. Therefore, the choice of the SS and the MS/opacity composites does not influence the aesthetic outcome of posterior restorations for the lighter shades. However, the use of bulk fill material for dark shades is less favorable than the MS layering ones.